Determination the Effect of Work Shift on Nurses’ Health working at Teaching Hospitals - Ali Abdul Lateef Fadhil, Raad Kareem Faraj (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: The study aims at assessing the level of work shit effect on nurses’ health and to find out the association between level of effect and demographic variables of nurses. Material and methods: A descriptive analytical study that is conducted for the period of October 1st 2021 to June 1st, 2022. The sample of the study includes 239 nurses were selected by convenient sampling method (non-probability sample). The setting of the study includes the teaching hospitals in Baghdad city. The questionnaire of the study is employed to fit the current study which consists of two parts; the first part is contained the covering letter and the socio-demographic variables; the second part is concerned with items related to effect of work shift on nurses’ health that comprised of 65 items distributed on eight dimensions. The data have been collected through the utilization of the self-administrative report as a mean of data collection. Statistical analyses were conducted by using statistical package for social science (IBM SPSS Statistics) version 26.0. Results: The study found that that 94% of nurses are associated with moderate level of effect regarding work shift (218.38±15.224). Nurses are associated with moderate level of fatigue and sleep disorder (38.84±5.798); moderate level of eating and social health problems (27.93±3.581); moderate level of psychological and social problems (47.43±5.791); moderate level of criteria of distributing work shift for nurses (17.12±2.996); moderate level of factors affecting work shift and controlling stress (26.12±3.691); high level of coping with work shift (19.82±3.019); moderate level of consequences related to work environment and job satisfaction (21.49±4.545); and moderate level of performance and safety from medical risks (19.63±3.446). There is significant correlation between effect of work shift and nursing qualification at p-value= .013 Conclusions: Based on the study finding, the study concludes that nurses are exposed to moderate level of impact related to work shift. Recommendations: The study is recommended that Ministry of Health should initiate incentives for nurses who are working during night and evening shift to encourage them and decrease their problems